Rapid implementation of virtual clinics due to COVID-19: report and early evaluation of a quality improvement initiative. Issue 2 (21st May 2020) - Gilbert, Anthony William; Billany, Joe C T; Adam, Ruth; Martin, Luke; Tobin, Rebecca; Bagdai, Shiv; Galvin, Noreen; Farr, Ian; Allain, Adam; Davies, Lucy; Bateson, John
Abstract : Background: The COVID-19 outbreak has placed the National Health Service under significant strain. Social distancing measures were introduced in the UK in March 2020 and virtual consultations (via telephone or video call) were identified as a potential alternative to face-to-face consultations at this time. Local problem: The Royal National Orthopaedic Hospital (RNOH) sees on average 11 200 face-to-face consultations a month. On average 7% of these are delivered virtually via telephone. In response to the COVID-19 crisis, the RNOH set a target of reducing face-to-face consultations to 20% of all outpatient attendances. This report outlines a quality improvement initiative to rapidly implement virtual consultations at the RNOH. Methods: The COVID-19 Action Team, a multidisciplinary group of healthcare professionals, was assembled to support the implementation of virtual clinics. The Institute for Healthcare Improvement approach to quality improvement was followed using the Plan-Do-Study-Act (PDSA) cycle. A process of enablement, process redesign, delivery support and evaluation were carried out, underpinned by Improvement principles. Results: Following the target of 80% virtual consultations being set, 87% of consultations were delivered virtually during the first 6 weeks. Satisfaction scores were high for virtual consultations (90/100 for patients and 78/100 for clinicians); however, outside of the COVID-19 pandemic, video consultations would be preferred less than 50% of the time. Information to support the future redesign of outpatient services was collected. Conclusions: This report demonstrates that virtual consultations can be rapidly implemented in response to COVID-19 and that they are largely acceptable. Further initiatives are required to support clinically appropriate and acceptable virtual consultations beyond COVID-19. Registration: This project was submitted to the RNOH's Project Evaluation Panel and was classified as a service evaluation on 12 March 2020 (ref: SE20.09).